Research, analysis, alternative methods of hot forging processing by pressure casting in the manufacturing of aluminum alloy female stem part - Nguyễn Chí Thành,; Huỳnh Nguyễn Hoàng, (Journal of Technical Education Science, 2012)
This paper address alternative methods of hot forging processing by pressure casting in the manufacturing of aluminum alloy female stem part. To research the author conducted a survey, analysis and experimental in Song Tain Industrial Co., Ltd. Our products are manufactured and tested by the following methods: check the weight with electronic weight scale, hardness testing by Webster Instrument (Model B) alkaline, flaw test by ultrasound machine, Check oxidation and test the durability of all. Research results show that the product achieved the quality requirements, when the production number of the product is higher than ~ 25000 samples, the method of pressure casting cost saving than when using hot forging method.